Transnasal Access for Sampling a Skull Base Lesion - Phadke, Rajendra (AJNR Am J Neuroradiol, 2001)
Summary: Transnasal needle access for sampling was used in two patients with posterior nasopharyngeal lesions. The procedure was performed under CT guidance. This new technique is simple and appears suitable for selected cases. The two cases and the details of the procedure are described.